Endurcissement du naissain d’huîtres creuses, Crassostrea gigas par le niveau d’exondation ou la densité d’élevage : récapitulatif d’essais conduits entre 2004 et 2007 en rivière d’Auray (56), pour réduire les mortalités estivales - Mazurie, Joseph; Bouget, Jean-francois; Langlade, Aime; Claude, Serge (2011)
This report summarizes a list of husbandry experiments conducted between 2004 and 2007 so as to reduce the summer mortalities of the oyster Crassostrea gigas by farming practices. The Japanese technique so‐called “hardening”, based on nursing the young oysters (less than 1 year‐old) in intertidal areas with high air exposure, is tested and adapted. Significant improvements of survival rates (e.g. 60% survival instead of 40% survival rate) have been obtained by transferring the spat only a few month (between march and june‐july) on “high” inter‐tidal farming plots (up to 40% of mean air exposure time). In such conditions, growth is transiently reduced, but a compensatory growth seems to happen when oysters are transferred back on low concessions. Another means of reducing growth, by increasing the density of oysters per bag, was not successful in terms of survival. The physiological effect induced by “hardening” oysters remain to be cleared and the technique tested in other sites before large scale application. Its benefit needs also to be tested in the new context of epidemic disease striking oyster cultures in France, since 2008. Ce rapport récapitule les essais menés entre 2004 et 2007 pour tenter de réduire les mortalités estivales de naissain de Crassostrea gigas, par les pratiques zootechniques et notamment celle qualifiée d’endurcissement. Il s’agit de prégrossir les huîtres dans des conditions de forte exondation (exondation par coefficient de marée de 30‐40), avant de les remettre sur parc normal d’élevage au début ou en cours d’été. Plusieurs années de suite, sur le même site en amont de la rivière d’Auray (Bretagne Sud, France), des améliorations de survie très significatives ont été ainsi obtenues. Les meilleurs résultats correspondent à un endurcissement de durée limitée (3‐4 mois, entre mars et juin‐juillet), pour lequel le ralentissement de croissance semble pouvoir être compensé une fois les huîtres ramenées au niveau bas d’élevage. Une tentative d’obtenir le même gain en bridant la croissance ...